Are We Working Harder for Less Pay? A Survey of Medicare Reimbursement for Hand and Upper Extremity Surgery. Issue 4 (14th February 2022) - Nayar, Suresh K.; Wollstein, Adi; Sullivan, Brian T.; Kreulen, R. Timothy; Sabharwal, Samir; Tuffaha, Sami H.; LaPorte, Dawn M.; Chen, Neal C.; Eberlin, Kyle R.
Abstract : Background: Ongoing concern for declining Medicare payment to surgeons may incentivize surgeons to perform more cases to maintain productivity goals. The authors evaluated trends in physician payment, patient charges, and reimbursement ratios for the most common hand and upper extremity surgical procedures. Methods: The authors examined Medicare surgeon payment, patient charges, and surgical volume from 2012 to 2017 for 83 common surgical procedures, incorporating the year-to-year Consumer Price Index to adjust for inflation. The reimbursement ratio was calculated by dividing payment by charge. Weighted (by surgery type and volume) averages were calculated. Results: Total Medicare surgeon payment increased 5.6 percent to $272 million for the studied procedures. Patient charges were seven times greater than payment, growing 24 percent to $1.9 billion. Despite growth of total payment, the average overall weighted payment for a single surgery decreased 3.5 percent. The average weighted patient charge increased 8 percent, whereas the reimbursement ratio decreased 13 percent. A hand surgeon would need to perform three more cases per 100 in 2017 to maintain the same reimbursement received in 2012. After categorizing these 83 surgical procedures, distal radius fixation (>3 parts, 21 percent increase; >2-part intra-articular, extra-articular, and percutaneous pinning, 17 percent increase), bony trauma proximal to the distal radius (10 percent increase), and upper extremity flap (5 percent increase) were subject to the greatest increases in payment. Payment for forearm fasciotomy (39 percent decrease), endoscopic carpal tunnel release (30 percent decrease), and mass excisions proximal to the wrist (18 percent decrease) decreased the most. Conclusions: From 2012 to 2017, despite a disproportionate increase in procedure charges, Medicare surgeon payment has not decreased substantially; however, total reimbursement is multifactorial and involves multiple sources of revenue and cost.